Kajian mengenalpasti isu dan punca konflik yang mempengaruhi tahap keharmonian masyarakat di Malaysia bagi tahun 2011 dan 2012 - Suraya, Wen (2014)
Nurturing and guarding a harmonious society in diversified and varied ethnic backgrounds should be a priority to ensure the level of harmony in the country is preserved at all times. Therefore a right approach to identify issue and source of conflict in the community is vital to avoid social conflict. Thus , this study aims to discover an improved method to identify issues that can be the sources of social conflicts. This study analyses validity and reliability of manifestation approach adopted by National Unity and Integration Department (NUID) in identifying issues and sources of social conflicts in Malaysian communities. The aim is to assist the department to adopt the right management methods and strategies to avoid more serious conflicts. Manifestation approach that refers to the Framework Development of the Stages of Conflict by Judith R. Gordon is adopted for this study. The research method is qualitative content analysis by taking data in an inductive interpretative approach.The findings of the research discovers that the existing approach in identifying issues and sources of social conflicts in the community can be improved by providing more precise definitions to ensure the collected data can be categorized accurately. The findings have obtained twelve categories of incidents and seven sections of issues that can be utilized to ensure the collected data are categorized accurately.The twelve categories are violence, riot, fight, attack, march, picket, protest, silent protest, hunger strike, sit-in, vigil and dispute. The seven identified sections of issues are religion, ethnicity, governance, safety, subsistence, environmental issues and global issues. The findings are expected to be able to assist NUID to rearrange the issues and sources of conflicts into more clearly defined categories. This will help the department to choose the right methods and strategies to manage social conflicts and to avoid more serious social conflicts in future.